TRENDS IN Y GENERATION’S BEHAVIOUR ON THE FOOD MARKET - Barbara Kucharska; Mirosława Malinowska (Polityki Europejskie, Finanse i Marketing)
The aim of the article is to identify Y generation’s behaviour on the food market in the context of dominant consumer trends. The purpose of the article was accomplished by literature studies, information from branch magazines and direct research carried out by the authors of the article. Identification of consumer trends was made on the basis of secondary sources of information, using also the report Top 10 Global Consumer Trends 2019 by Euromonitor International. The report also became an inspiration to undertake direct research, which was carried out using the auditorium survey technique among representatives of the Y generation. The results of research and analysis indicate that the Y generation referred to as "yummy" is an extremely important entity on the food market - large, young, innovative , active, fast, demanding, unique and very important for the supply entities on the food market. The behaviour of this group of consumers determines contemporary trends on the market and the necessity to undertake activities consistent with these trends in terms of the offer, its availability, as well as diversity and price.